(Structure Logistic Regression Model Of Anomalies Birth In Iraq Except Kurdistan Region, for 2015) - كمال غفران اسماعيل; كاظم زينب جواد (Journal of Economics and Administrative Sciences, 2019)
Congenital anomalies commonly occur in humans, possibly visible. If these anomalies appear in visible parts in human body such as face, hands and feet. They may only appear after utilizing a number of special tests in order to show by means of the anomalies that occur in the internal organs of the body such as heart, stomach and kidneys. Research data have comprised accessible information in the anomalies birth statistics form situated of Health and Life Statistics section at the Ministry of Health and environment, where the number of anomalies births involved in the study (2603 anomalies birth) in Iraq, except Kurdistan region, at 2015. A two way-response logistic regression analysis has been applied of the dependent variable (y) type of deformation (simple, Complex) and estimation of its parameters in the greatest possible way (ML). Test significance of model as well as the significance of parameter information that reached the six variables affecting determinant of anomaly type of (sex of male type, sex of female type, the degree of relationship existence- type, profession of father of governmental employee-type, type of previous birth to a live birth type, and a former anomaly premature birth).